Establishing a culture of limno-terrestrial tardigrada in laboratory and development of alternative - Silvana Perissato Meneghin; André Arashiro Pulschen (Universidade do Oeste de Santa Catarina, 2010)
Tardigrades (Phylum Tardigrada) are invertebrate animals also known as water bears, that occurs almost in everylocations on Earth, from the Arctic to Antarctic, from Himalayan top to the bottom of the ocean. One of the reasonsthat the animals can live in such places lays on his cryptbiotical hability, state that it’s induced by hard conditions.In such state, they can survive desiccation, temperatures from -192 °C and up to 100 °C, pressure of 7500 Pa,radiation levels of 7000 Gy and another’s conditions. Currently, the phylum has been deeply investigated, sincethe cryptobotical phenomenon it’s extremely interesting from the point of view of Biotechnology. The phylum it’salso important to metazoan phylogeny studies, evolutionary studies and to astrobiology. There is no relates fromcryptobiotical studies and lab rearing of tardigrades in Brazil, so this is the first work of the genera. The presentwork had as objectives: establishing a rearing system of a limno-terrestrial Tardigrade and also the developmentof alternatives methods of dissecation of the animals, alternatively the use of dessicators and chemical solutions. Ithas been established successfully a culture of the Tardigrada Macrobiotus hufeandi, using the microalgae Chlorellavulgaris as food, in small plastic containers of about 30 mm diameter and 20 mm in height, with water and foodbeing exchanged every two days. The proposed methods of dehydration achieved survivor rates of 70 and 77%,similar results of existing studies in the literature and may be simpler alternatives to anhydrobiosis studies.Keywords: Tardigrada. Lab rearing. Cryptobioses. Dessication.